2022
DOI: 10.21521/mw.6672
|View full text |Cite
|
Sign up to set email alerts
|

Horses’ perception of a threat posed by sounds of different origin

Abstract: The aim of the study was to assess the behavioural reaction and emotional arousal of warmblood horses in response to sounds of different origin, and to classify those sounds into neutral ones, those causing a behavioural change and those causing a behavioural and physiological stress response. We tested the hypothesis that the perception of a sound as neutral or potentially threatening does not simply depend on the sound origin per se, but rather on the context in which the sound occurrs (predictability), addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These circumstances had an impact on HRV changes, but the response was delayed. Another reason for these differences may be the measurement time—5 min in the previous [ 31 ] and 1 min in the current study.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…These circumstances had an impact on HRV changes, but the response was delayed. Another reason for these differences may be the measurement time—5 min in the previous [ 31 ] and 1 min in the current study.…”
Section: Discussionmentioning
confidence: 74%
“…HRV reflects the modulating effect of ANS on cardiac responses [ 37 ]. In the previous study [ 31 ], we showed that a 1-min recording was not sufficient to influence HRV responses (RMSSD, LF, HF, LF/HF), and mainly only HR and RR changes were noted. In that particular case, horses were in the known paddock in a group and were not supposed to border a line.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Two different sounds were used during these tests: sound A (squeal of a pig, produced during distress (Çavuşoğlu et al 2020 )) and sound B (futuristic characteristics; similarity to radio and TV interference, crackling). The sounds were selected based on the results of our previous studies: comparing reaction to 40 sounds of different origin (Janicka et al 2022a ), assessing the possibility to use sound stimulus in creating virtual barrier (Janicka et al 2022b ) and comparing reactions to 40 known and four novel sounds (unpublished data). Sounds that were chosen elicited similar and strongest avoidance behaviour.…”
Section: Methodsmentioning
confidence: 99%